2015
DOI: 10.1007/s12012-015-9343-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, Antithrombotic and Cardiac Remodeling Preventive Effects of Eugenol in Isoproterenol-Induced Myocardial Infarction in Wistar Rat

Abstract: This study aimed to evaluate the antithrombotic, anti-inflammatory and anti-cardiac remodeling properties of eugenol in isoproterenol-induced myocardial infarction in rats. Male Wistar rats were randomly divided into four groups, control, iso [100 mg/kg body weight was injected subcutaneously into rats at an interval of 24 h for 2 days (6th and 7th day) to induce MI] and pretreated animals with clopidogrel (0.2 mg/kg) and eugenol (50 mg/kg) orally for 7 days and intoxicated with isoproterenol (Iso + Clop) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
5
30
0
1
Order By: Relevance
“…Meanwhile, the obtained results proved that co‐treatment with FWEP ameliorated the status of TMX‐induced cardio toxicity in rats through maintaining cardiac biomarker enzymes to a near normal condition. This underlines that FWEP is responsible for the protection of the structural and architectural integrity of cardiomyocytes by preventing lipid peroxidation owing to its ability to scavenge superoxide and hydroxyl radicals as reported by our in vitro study through via FWEP linoleate model system confirmed by Ktari et al In this regard, previous investigations demonstrated that polysaccharide could correct dyslipidemia, improve TG metabolism, enhance endothelial function, increase antioxidant potential and decrease LDL …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Meanwhile, the obtained results proved that co‐treatment with FWEP ameliorated the status of TMX‐induced cardio toxicity in rats through maintaining cardiac biomarker enzymes to a near normal condition. This underlines that FWEP is responsible for the protection of the structural and architectural integrity of cardiomyocytes by preventing lipid peroxidation owing to its ability to scavenge superoxide and hydroxyl radicals as reported by our in vitro study through via FWEP linoleate model system confirmed by Ktari et al In this regard, previous investigations demonstrated that polysaccharide could correct dyslipidemia, improve TG metabolism, enhance endothelial function, increase antioxidant potential and decrease LDL …”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, our in vivo experimental study revealed that TMX induced myocardial damage in rats. When, myocardial cells are damaged, the cardiac membrane becomes permeable inducing enzyme leakage . In the current study, the significant increase in plasma biomarker activities has been recorded in TMX group compared to control.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The TUNEL staining showed marked TUNEL + apoptotic cells in the injured muscles of CatK +/+ mice on Day 3 after the CTX injection, and this change was prevented by CatK deletion (Figure A and B). Plasma LDH levels have often been used to predict muscle injury in humans and animals . To further examine the difference in muscle injury, the plasma LDH levels were analysed by enzyme‐linked immunosorbent assay.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma LDH levels have often been used to predict muscle injury in humans and animals. 39 To further examine the difference in muscle injury, the plasma LDH levels were analysed by enzyme-linked immunosorbent assay. The quantitative biological analysis revealed significantly lower levels of plasma LDH from the CatK À/À mice compared with that from the CatK +/+ mice ( Figure 3C).…”
Section: Cathepsin K Deficiency Mitigated the Cardiotoxin-induced Celmentioning
confidence: 99%